EMPATI ANAK JALANAN DI SEKITAR LAMPU MERAH GRAMEDIA KOTA PEKANBARU - Diana Dwi Handayani; Rosmawati Rosmawati; Siska Mardes (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2020)
Abstract: this determination is carried out around the Gramedia red light Pekanbaru City. The purpose of this study was to determine the characteristics and empathy of street children around the red light Gramedia Pekanbaru, in this study used a descriptive research type with predetermined indicators, and ways of collecting and calculating research data with a qualitative approach. In order to get information, the researchers took informants. And the informants of this research are street children around the red light Gramedia Pekanbaru city. Data collection techniques in this study using interview techniques, observation, documentation. After conducting this research, it is known that the empathy of street children around the red light Gramedia Pekanbaru city still has a sense of empathy for the surrounding environment.Keywords: Empathy, Characteristics, And Street Children.